Modelowanie kosztów obiektów kosztowych w rachunku kosztów działań - Kowalski, Michał Jerzy (Model of the Cost Objects' Expenditure in an Activity Based Costing, 2007)
The article treats the problem of modeling the costs of cost objects in the Activity Based Costing. The current state of knowledge is presented and the issues which still need solutions emphasized. The author propose a formal description, definitions and a graphical notation to model the costs of cost objects. The article also describes the application of some issues referring to the entity-relationship modeling to solve the identified problems. A practical example presenting the application of the presented proposals is also included. (
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 310-321